MUTU LAYANAN AKADEMIK JURUSAN TARBIYAH DAN KEGURUAN STAIN TEUNGKU DIRUNDENG MEULABOH - Siti Hajar; Dian Ayuningtyas; Junias Zulfahmi (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2025)
The purpose of this study was to determine the quality of academic services for the Tarbiyah and Teacher Training Department and the constraints in providing services to the academic Tarbiyah and Teacher Training Department of STAIN Teungku Dirundeng Meulaboh. This study used descriptive qualitative method. Sampling used purposive sampling technique for taking interview informants and simple random sampling technique for student samples.Data collection uses interview techniques, questionnaires and documentation, while the analysis uses the stages of reduction, data reduction and drawing conclusions. The results showed that the academic services of the Tarbiyah and Teacher Training Department of STAIN Teungku Dirundeng Meulaboh were good. The provision of academic services includes academic services and non-academic services which are all related to the lecture process.This is also supported by the tangible dimension of 55%, the reliability dimension of 88.8%, the responsiveness dimension of 72.5%, the empathy dimension of 86.19 and the assurance dimension of 86.67%. Constraints in providing services to the academic Tarbiyah and Teacher Training Departments of STAIN Teungku Dirundeng Meulaboh, namely physical facilities and infrastructure that are still lacking in lectures, network problems due to information conveyed to students through the WA group and problems with students themselves who do not want to face directly to the academic department , majors and study programs to solve the problem.